ANALISIS STATISTIKA DALAM PENGELOLAAN DATA DAN NILAI RAPORT DI SDN PEGANGSAAN DUA 07 - Nurhasanah, Wulan Dari Fitriani, Neti Nur Febriawati, Burhanudin Soleh, Yohanes Riski Siregar, Riza (CV. ADIBA AISHA AMIRA, 2024)
This research aims to identify the methods used by teachers in processing data and student report cards. Data collection techniques include observation and interviews. Observations are used to study how teachers process data and student grades, while interviews are conducted to gain an in-depth understanding of teachers' data processing methods and report card grades. The research results show that teachers use various forms of data presentation such as tables, symbol diagrams, bar diagrams, line diagrams and circle diagrams in processing student data. Processing of report cards is carried out with the help of tables and Microsoft Excel software.